Discrimination between natural and induced seismicity in the Hengill geothermal area, SW Iceland - Rossi, Camilla <1992> (Alma Mater Studiorum - Università di Bologna, 2021)
The Hengill area is a complex tectonic and geothermal site, located at the triple junction between the Reykjanes Peninsula (RP), the Western Volcanic Zone (WVZ), and the South Iceland Seismic Zone (SISZ). Geothermal systems in the vicinity of the Hengill volcano are exploited for electrical power and heat production, and today the two largest operating geothermal power plants are located at the Nesjavellir and the Hellisheiði. The region is seismically highly active with several thousand earthquakes located yearly, and whose origin may be either natural or anthropogenic. The thesis focuses on the analysis and investigation of the